Nabuco, um diálogo em aberto - Nogueira, Marco Aurélio [UNESP] (Centro Brasileiro de Análise e Planejamento, 2010)
O artigo explora o legado de Joaquim Nabuco e argumenta que sua atuação política, diplomática e intelectual tem algo a nos dizer sobre as questões e os dilemas com que nos debatemos hoje, em nossa República consolidada, antes de tudo sobre o modo como temos praticado (ou não) a reforma social e buscado construir uma sociedade que inclua todos os seus integrantes.

The article explores the legacy of Joaquim Nabuco and suggests that his political, diplomatic and intellectual involvement with the questions of his time has something to say about the dilemmas we face today as a society, in our established Republic - above all, about the way Brazilian society has implemented (or has failed to implement) the needed social reforms and has sought to build a society that is able to integrate all of its citizens.
Keywords: Joaquim Nabuco; reforma social; desigualdade; Brasil contemporâneo; Joaquim Nabuco; social reform; inequality; contemporary Brazil